Features of psychological counseling with victims of human trafficking who have committed suicide attempts - Maxmudova Dilarom Axmadovna; Rustamjonova Muharramkhon (Zien Journals, 2022)
The article reveals the features of psychological counseling with victims of human trafficking who have committed suicide attempts.
Keywords: age period; development; suicide; personality